The innovation killer : how what we know limits what we can imagine-- and what smart companies are doing about it - Rabe, Cynthia Barton (Amacom, 2006)
Knowledge is good," preaches the inscription under the statue of college founder Emil Faber in the film Animal House. But as valid as that declamation may be at a university, in the corporate world what passes for knowledge can be a killer. Companies and teams rely on "what we know" and "the way we do things here" to speed decision making and maintain a sense of order. But progress demands change, risk taking, and occasionally, revolution. Processes must be overhauled, assumptions challenged, taboos broken. But how do you do it? Who among the group will take responsibi.